Application for patent stabilized cassava gel and its production technique (2021)
An invention in the production of a stabilised, and durable gel (having a long shelf-life of about two years), from cassava starch for applications as sizing-agent in pulp and paper making, wood-composites production, textile/laundry services and other relevant uses is presented. The new product called KAMOGEL is made by combining the pre-mixed and pre-determined quantities of cassava starch, water, preservatives, stabiliser/emulsifier, and essential oil sequentially.